Život i stvaralaštvo Drage Gervaisa u hrvatsko-slovenskom kontekstu: Čudo djevice Ivane – Zgodba o Vodiški Johanci - Jurdana, Vjekoslava (Slavia Centralis, 2020)
Life and work of Drago Gervais in the Croatian-Slovenian context: Miracle of a Virgin Ivana - The story of Vodiška Johanca
Keywords: Drago Gervais; Croatian-Slovenian context; Ivanka Jerovšek; The Virgin Joanna's Miracle